Beyond the prophecy success: how place attachment and future time perspective shape rural university students intentions of returning to small islands - Simões, F.; Rocha, R.; Mateus, C. (Journal of Youth Studies, 2020)
Rural areas are struggling with youth mobility to urban centers. We address this challenge by testing the interplay between objective factors underlying mobility, namely socio-economic status indicators, and subjective factors, specifically Place Attachment (PA) and Future Time Perspective (FTP), and how they connect with the returning intentions of university students with a rural background after their graduation. We also explore how the connections between these variables vary across gender. Our study involved 337 university students (M = 21.55; SD = 2.48; 63.50% female) enrolled in tertiary education in mainland Portugal. The participants were from The Azores Islands, a remote and mostly rural Portuguese region. Using a Structural Equation Model (SEM) and Multi-Group Analysis (MGA) approach, we found that greater PA significantly improved their prospects of returning, rather than greater expected monthly income 3 years after graduation. However, these trends were only relevant among young women. Our findings indicate the need to strengthen youth civic engagement policies, as well as new youth employment packages that diversify the transition from education to the labor market or better match local resources with more promising and rewarding careers.